Highway embankment construction using fly ash and snow in cold regions - Saygılı, Altuğ. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
During winter season, due to workability problems, it is very hard to continue construction. Water needed for compaction will be very hard to handle. However, snow is readily available on site. With Type C fly ash, snow may be mixed with fly ash and compacted. Due to its silt size one or two per cent wet of optimum water content makes the compaction of fly ash impractical. An excess amount of water is needed to enhance reactions leading to formation of cementitious products, which increases strength. A new technology has been developed to add more water into fly ash samples to enhance the pozzolanic reactions, leading to cementitious mineral formation. Fly ash at optimum water content and fly ash with additional 10 per cent by weight of snow were compacted, sealed and cured for one, seven, 14, 28, and 90 days at 21C. Unconfined compression, splitting tensile and hydraulic conductivity tests were conducted. The initial hydration process has been investigated using infrared thermography. Gamma-spectroscopic analysis techniques were used to determine 238U, 235U, 226Ra, 232Th. The dosimetric calculations are reported. The addition of snow into fly ash increased the unconfined compressive strength and splitting tensile strength noticeably beginning from 14 days of curing reaching up to two times that of control samples at the end of 90 days of curing. The hydraulic conductivity increased two to three orders of magnitude for snow-added samples. Gamma radiation has decreased 30 to 40 per cent of that of control samples. XRD and ESEM examinations provided detailed information about the microstructural development of the tested specimens. Snow addition had a remarkable effect on improving the freeze-thaw and thermal conductivity properties of the compacted fly ash specimens. The leaching fluid quality data indicated that the leachate from the control fly ash and snow added fly ash had no discernable impact on ground water quality. With its higher void ratio, lighter weight, higher strength, higher hydraulic conductivity, lower gamma radiation and higher freezethaw performance, the proposed technique may be beneficial for highway agencies exposed to rough winter conditions in two ways; construction activities will not be ceased during snow, a higher performance road construction material will be obtained.
Keywords: Highway engineering.; Roads -- Design and construction.; Fly ash.